Clinical heterogeneity and phenotype/genotype findings in 5 families with GYG1 deficiency. (December 2017) - Ben Yaou, Rabah; Hubert, Aurélie; Nelson, Isabelle; Dahlqvist, Julia R.; Gaist, David; Streichenberger, Nathalie; Beuvin, Maud; Krahn, Martin; Petiot, Philippe; Parisot, Frédéric; Michel, Fabrice; Malfatti, Edoardo; et al.
Abstract : Objective: To describe the variability of muscle symptoms in patients carrying mutations in the GYG1 gene, encoding glycogenin-1, an enzyme involved in the biosynthesis of glycogen, and to discuss genotype-phenotype relations. Methods: We describe 9 patients from 5 families in whom muscle biopsies showed vacuoles with an abnormal accumulation of glycogen in muscle fibers, partially α-amylase resistant suggesting polyglucosan bodies. The patients had either progressive early-onset limb-girdle weakness or late-onset distal or scapuloperoneal muscle affection as shown by muscle imaging. No clear definite cardiac disease was found. Histologic and protein analysis investigations were performed on muscle. Results: Genetic analyses by direct or exome sequencing of the GYG1 gene revealed 6 different GYG1 mutations. Four of the mutations were novel. They were compound heterozygous in 3 families and homozygous in 2. Protein analysis revealed either the absence of glycogenin-1 or reduced glycogenin-1 expression with impaired glucosylation. Conclusions: Our report extends the genetic and clinical spectrum of glycogenin-1–related myopathies to include scapuloperoneal and distal affection with glycogen accumulation.